2022
DOI: 10.1021/acssuschemeng.1c06327
|View full text |Cite
|
Sign up to set email alerts
|

High-Value Recycling of Isotactic Polypropylene-Based Plastic Waste as a Crystallization Promoter for High-Performance Polypropylene Random Copolymers

Abstract: Highly efficient recycling of nonrenewable resources is increasingly important at the global concern of resource crisis and environmental issue. Here, a new strategy for value-added application of isotactic polypropylene (iPP)-based plastic waste as a crystallization promoter was proposed, and cigarette packaging film (CPF) waste as a typical single-component iPP was used as a representative example to demonstrate the successful application. First, the CPF wastes were pulverized into ultrafine powders under th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…The sharp decrease of the average size (from millimeter level to micrometer level) indicated that efficient pulverization could be successfully achieved at room temperature, attributed to the strong shearing and squeezing force generated from the unique three-dimensional scissor structure of the two close rotating pans. In this way, the well-pulverized chitin powders could be obtained on a large scale through this unique S 3 M equipment, which possessed a high production exceeding 150 kg/h, showing higher efficiency and more cleanliness in comparison to the conventional milling methods. As shown in Figure d–f, the number of the large-sized chitins decreased, and chitin powder size continuously decreased with the increasing milling cycle, along with the improvement of the size distribution uniformity .…”
Section: Resultsmentioning
confidence: 99%
“…The sharp decrease of the average size (from millimeter level to micrometer level) indicated that efficient pulverization could be successfully achieved at room temperature, attributed to the strong shearing and squeezing force generated from the unique three-dimensional scissor structure of the two close rotating pans. In this way, the well-pulverized chitin powders could be obtained on a large scale through this unique S 3 M equipment, which possessed a high production exceeding 150 kg/h, showing higher efficiency and more cleanliness in comparison to the conventional milling methods. As shown in Figure d–f, the number of the large-sized chitins decreased, and chitin powder size continuously decreased with the increasing milling cycle, along with the improvement of the size distribution uniformity .…”
Section: Resultsmentioning
confidence: 99%
“…However, while changes in T m are directly related to M w , changes in crystallization temperature T c may be influenced by various factors such as cooling rate, nucleation agents and interfaces. 7 The presence of GL retards the crystallization process in unexposed specimens, while it appears to facilitate crystallization upon irradiation. Heterogeneous microdomains can act as nucleation sites in PP, 45 but the influence of UV irradiation on this process in lignin compounds remains unclear based on our current data and thus requires further study.…”
Section: Resultsmentioning
confidence: 99%
“…Although cost-effective and high-performance "renewable" polymers (i.e., bio-based or bio-degradable) are ideal and recent progress in their development is encouraging, an immediate strategy is needed for improving the sustainability of polyolens currently in circulation-i.e., upcycling and recycling. 6,7 Owing to their continuous hydrocarbon backbone structure, poly-olens are chemically stable against a wide variety of organic solvents and reagents and thus cannot be chemically recycledi.e., returned to monomers/oligomers-without changing the chemical structure. 8,9 A common disposal route for polyolens in the EU and USA consists of incineration (termed "thermal recovery") for the purpose of utilizing the released thermal energy, consequently releasing additional CO 2 as well.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by the Chinese stone-mill, a solid-state shear milling (S3M) equipment was designed, with numerous bevel ridges similar to three-dimensional scissors, exerting strong squeezing and shearing forces on the milling material (Wu et al, 2022). In this way, ultra ne pulverization of ductile polymers and uniform dispersion of heterogeneous materials may be achieved in preparing high-performance composites (Song et al, 2021;Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%